2016
DOI: 10.26493/1855-3974.909.0e1
|View full text |Cite
|
Sign up to set email alerts
|

The distinguishing index of the Cartesian product of finite graphs

Abstract: The distinguishing index D (G) of a graph G is the least natural number d such that G has an edge colouring with d colours that is only preserved by the identity automorphism. In this paper we investigate the distinguishing index of the Cartesian product of connected finite graphs. We prove that for every k ≥ 2, the k-th Cartesian power of a connected graph G has distinguishing index equal 2, with the only exception D (K 2 2) = 3. We also prove that if G and H are connected graphs that satisfy the relation 2 ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Another open problem is a lower bound for the sizes of graphs G and H that implies that D (G × H) ≥ d (or D (G H) ≥ d, respectively) for a given integer d. A corresponding result for D (G2H) was proved in [4].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another open problem is a lower bound for the sizes of graphs G and H that implies that D (G × H) ≥ d (or D (G H) ≥ d, respectively) for a given integer d. A corresponding result for D (G2H) was proved in [4].…”
Section: Discussionmentioning
confidence: 97%
“…As the distinguishing index of the Cartesian powers of graphs has been studied in [4], then higher powers of cycles, and of other graphs, with respect to the direct and strong product can be considered. Note that even cycles are bipartite, and the direct product of bipartite graphs is disconnected (if the number of isomorphic components of a graph G is large enough, then the distinguishing index of G is greater than that of a single component).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We call every C 4 in the book graph B n , a page of B n . The distinguishing index of Cartesian product of star K 1,n with path P m for m 2 and n 2 is D ′ (K 1,n P m ) = ⌈ 2m−1 √ n⌉, unless m = 2 and n = r 3 for some integer r. In the latter case D ′ (K 1,n P 2 ) = 3 √ n + 1, ( [6]). Since B n = K 1,n ✷P 2 , using this equality we obtain the distinguishing index of book graph B n .…”
Section: The Distinguishing Chromatic Index Of Certain Graphsmentioning
confidence: 99%
“…Imrich and Klavzar in [6], and Gorzkowska et.al. in [2] showed that the distinguishing number and the distinguishing index of the square and higher powers of a connected graph G = K 2 , K 3 with respect to the Cartesian product is 2.…”
Section: Introduction and Definitionsmentioning
confidence: 99%